Chemical modification of hydrotalcite coating for enhanced corrosion resistance. (April 2015) - Wang, Lida; Zong, Qiufeng; Sun, Wen; Yang, Zhengqing; Liu, Guichang
Highlights: Hydrotalcite serves as a template for chemical modification of the coating. Microstructures of hydrotalcite are preserved after chemical modification. Intercalated corrosion inhibitor results in the phase conversion of hydrotalcite. Chemical modification effectively enhanced the chemical stability of the coating. Released corrosion inhibitor confers self-healing protection function on the coating. Abstract: This work provided a facile strategy to enhance the corrosion resistance of hydrotalcite coating by the chemical modification of the coating with 8-hydroxyquinolate anions. It shows that the chemical modification treatment induces the phase conversion of hydrotalcite coating by the intercalation of corrosion inhibitor into the coating. The hydrotalcite coating with unique layer micro/nanostructure not only serves as an effective template for the chemical modification of the coating, but also acts as a reservoir for the enhanced corrosion protection performance by releasing the accommodated corrosion inhibitor, when it suffers from local corrosion attack in aggressive environments.